Matt coating slurry, matte coating and LED display module

By using a matte coating slurry composed of nanoparticles, the problem of ink color in the module in COB packaging technology is solved, and the ink color consistency, simplicity of production and low cost are achieved.

CN119875468APending Publication Date: 2025-04-25UNILUMIN GRP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510054212.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In COB packaging technology, the color difference between PCB substrates of different manufacturers or batches leads to ink inconsistent problems in the packaged LED modules, affecting the visual effect and viewing experience.

Method used

The matte coating is made of nanoparticles as heterostructure, including mesoporous silica and black material. The matte coating formed by combining high-hardness resin, curing agent, nanoparticles, superdispersant and dilution solvents has functions such as anti-glare, anti-reflection and black underfill.

Benefits of technology

It effectively solves the problem of ink color difference between modules, simplifies the production process, improves product yield, and greatly reduces production costs, while ensuring the hardness and wear resistance of the coating material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875468A_ABST
    Figure CN119875468A_ABST
Patent Text Reader

Abstract

The invention provides a matte coating slurry. Compared with the prior art, the matte coating slurry provided by the invention is a phase separation system, and nanoparticles are neatly distributed on the surface of a coating material in the curing process of the coating material; the mesoporous silica with light diffusion and anti-reflection effects and the black nanoparticles with an ink color improving function are ingeniously and organically combined on the nanoscale, so that the single nanoparticle integrates multiple functions of light diffusion, anti-reflection, blackness improvement and the like; in addition, only a small adding amount of the nano-particles is needed, and the hardness and wear resistance of the coating material are guaranteed to the maximum extent; and finally, the nanoparticles can provide uneven microstructures for the matte coating to achieve an anti-dazzle effect, and meanwhile, due to the nanoscale particle size, particle sedimentation caused by the gravity action can be effectively reduced, so that the stability of the multifunctional matte coating slurry is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of LED display screens, and in particular relates to a matte coating slurry, a matte coating and an LED display module. Background Art

[0002] COB (Chips on Board) packaging, or chip-on-board packaging technology, refers to fixing multiple LED light-emitting chips directly on a PCB substrate and then using resin materials for overall packaging. It has many advantages, including simple production process, high heat dissipation efficiency, and fine image quality. With the continuous iteration and maturity of COB packaging technology, its production cost is decreasing day by day, and it is gradually replacing the traditional SMT (Surface Mount Device) surface mounting technology and becoming a new development trend.

[0003] Due to the color differences of PCB substrates from different manufacturers or batches, the modules after encapsulation often have inconsistent ink colors. After being spliced ​​into a large screen, the ink color differences between the modules in the off state greatly affect the visual effect and viewing experience, becoming one of the core issues that determine the competitiveness of the product. At present, the mainstream technical solution to this problem is to add melanin to the encapsulation resin to prepare a black semi-transparent encapsulation layer, or to spray black ink on the PCB substrate or the surface of the encapsulation layer. However, these treatment methods have a common problem, that is, the amount of melanin added: when the amount of melanin doping is small, it cannot effectively cover the ink color differences between the modules. When the amount of melanin added is large, it is easy to disperse unevenly and cause agglomeration, further deepening the ink color differences. Moreover, the greater the amount of melanin added, the greater the light decay, the lower the brightness of the display, further reducing the contrast of the screen, and at the same time not conducive to energy saving and environmental protection.

[0004] Therefore, it is necessary to design a new coating material with a simple process to efficiently solve the problem of ink color differences between modules. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a matte coating slurry, a matte coating and an LED display module. The matte coating formed by the matte coating slurry has the functions of anti-glare, anti-reflection and black bottom filling.

[0006] The present invention provides a matte coating slurry, comprising:

[0007]

[0008] The nanoparticles are nano heterogeneous structures;

[0009] The nanoparticles include mesoporous silica and a black material.

[0010] Preferably, the particle size of the nanoparticles is 3 to 200 nm.

[0011] Preferably, the black material is selected from one or more of carbon black, black quantum dots, ferroferric oxide, cobalt trioxide, dopamine, graphene and carbon nanotubes.

[0012] Preferably, the nanoparticles are of a core-shell structure;

[0013] The core of the nanoparticle is mesoporous silica, and the shell is a black material;

[0014] Alternatively, the core of the nanoparticle is a black material and the shell is mesoporous silica;

[0015] The shell thickness of the nanoparticles is 1 to 50 nm.

[0016] Preferably, the surface of the nanoparticle is provided with a modification group or a modification layer; the modification group is selected from one or more of amino, epoxy, vinyl and thiol;

[0017] The modified layer is selected from one or more of polyethyleneimine, polyvinyl alcohol, polyethylene glycol and paraffin.

[0018] Preferably, the high hardness resin is selected from one or more of medium and low temperature curing epoxy resin, moisture curing resin, UV curing resin and acrylic resin;

[0019] The medium and low temperature curing epoxy resin is selected from one or more epoxy resins with one or more of dicyandiamide curing agents, polyamide curing agents, tertiary amine curing agents, fatty amine curing agents, acid anhydride curing agents and imidazole curing agents as curing agents;

[0020] The moisture-curable resin is selected from one or more of epoxy resin, silicone resin and polyurethane resin;

[0021] The UV curable resin is selected from acrylate resin;

[0022] The curing agent is selected from one or more of dicyandiamide curing agents, polyamide curing agents, tertiary amine curing agents, fatty amine curing agents, acid anhydride curing agents and imidazole curing agents;

[0023] The super dispersant is selected from one or more of active derivatives based on a polyester main chain structure, polyurethane dispersants, grafted polyacrylate copolymers and polyether dispersants;

[0024] The diluting solvent is selected from one or more of toluene, xylene, n-hexane, ethyl acetate, ethanol, acetone, methyl ethyl ketone, cyclohexanone, methyl isobutyl ketone, ethylene glycol, chloroform, isopropanol, n-butanol, styrene, dibutyl phthalate, dioctyl phthalate, phenyl glycidyl ether, allyl glycidyl ether, p-cresol glycidyl ether, glycidyl methacrylate, ethylene glycol bisglycidyl ether, styrene oxide and alicyclic epoxy.

[0025] The present invention also provides a matte coating formed by the above-mentioned matte coating slurry.

[0026] Preferably, the thickness of the matte coating is 3 to 30 microns;

[0027] The visible light reflectivity of the matte coating is less than 2%.

[0028] The present invention also provides an LED display module, comprising a substrate, a plurality of LED light-emitting chips arranged on the substrate, a transparent packaging layer arranged between and on the upper surface of the plurality of LED light-emitting chips, a black light-transmitting adhesive film layer arranged on the transparent packaging layer, and a matte coating layer arranged on the black light-transmitting adhesive film layer; the matte coating layer is formed by the matte coating slurry described in any one of claims 1 to 6.

[0029] Preferably, the overall visible light transmittance of the LED display module is greater than 30%;

[0030] The visible light transmittance of the black light-transmitting adhesive film layer is greater than 30%.

[0031] The present invention provides a matte coating slurry, including: 50-100 parts by weight of high-hardness resin; 0-60 parts by weight of curing agent; 0.1-8 parts by weight of nanoparticles; 0.1-20 parts by weight of hyperdispersant; 5-20 parts by weight of diluent; the nanoparticles are heterogeneous nanostructures; the nanoparticles include mesoporous silica and black material. Compared with the prior art, the matte coating slurry provided by the present invention is a phase separation system. During the curing process of the coating material, the nanoparticles are neatly distributed on the surface of the coating material, avoiding the ink color difference caused by the inconsistent spraying thickness of the coating material; and the nanoparticles cleverly combine the mesoporous silica with light diffusion and anti-reflection effects and the black nanoparticles with ink color improvement function at the nanoscale, so that a single nanoparticle integrates multiple functions such as light diffusion, anti-reflection, and blackness enhancement, and further enables a single matte coating to have anti-glare coating, anti-reflection coating, and black background at the same time. The effect of functional coatings such as filling coatings has effectively simplified the production process, improved product yield, and greatly reduced production costs; in addition, nanoparticles only need to be added in a small amount to achieve the corresponding ink color regulation effect, thereby maximizing the hardness and wear resistance of the coating material; finally, nanoparticles can provide an uneven microstructure for the matte coating, thereby achieving an anti-glare effect. At the same time, due to their nano-level particle size, they can effectively reduce the particle sedimentation caused by gravity, thereby effectively improving the stability of the multifunctional matte coating slurry. In addition, their nano-size can also greatly improve the surface feel of the coating material. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 A schematic diagram of the cross-sectional structure of an LED display module provided by the present invention;

[0033] Figure 2 A schematic diagram of the preparation process of the LED display module provided by the present invention;

[0034] Figure 3 Schematic diagram of the structure of the paraffin-coated multifunctional nanoparticles Fe3O4@SiO2@paraffin prepared in Example 1 of the present invention;

[0035] Figure 4 This is a scanning electron microscope image of the paraffin-coated multifunctional nanoparticles Fe3O4@SiO2@paraffin prepared in Example 1 of the present invention;

[0036] Figure 5 Schematic diagram of the structure of the PEG-modified multifunctional nanoparticle SiO2@C-PEG prepared in Example 2 of the present invention;

[0037] Figure 6 This is a scanning electron micrograph of the PEG-modified multifunctional nanoparticle SiO2@C-PEG prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] The present invention provides a matte coating slurry, comprising:

[0040]

[0041] The nanoparticles are nano heterogeneous structures;

[0042] The nanoparticles include mesoporous silica and a black material.

[0043] According to the present invention, the content of the high hardness resin in the matte coating slurry is preferably 60 to 90 parts by weight, more preferably 65 to 85 parts by weight, and even more preferably 70 to 80 parts by weight.

[0044] According to the present invention, the high-hardness resin is preferably a high-hardness resin with a hardness of 6H or above after complete hardening, and there is no special limitation. In the present invention, it is preferably one or more of medium and low temperature curing epoxy resin, moisture curing resin, UV curing resin and acrylic resin; the medium and low temperature curing epoxy resin is preferably an epoxy resin with a curing temperature below 120°C, and more preferably one or more of epoxy resins with one or more of dicyandiamide curing agent, polyamide curing agent, tertiary amine curing agent, fatty amine curing agent, acid anhydride curing agent and imidazole curing agent as curing agent; the moisture curing resin is preferably one or more of epoxy resin, silicone resin and polyurethane resin; the UV curing resin is preferably acrylate resin; when the high-hardness resin is a UV curing resin, the matte coating slurry preferably also includes UV photoinitiator; the UV photoinitiator is a UV photoinitiator well known to those skilled in the art, and there is no special limitation. In the present invention, it is preferably one or more of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester, 2-dimethylamino-2-benzyl-1-[4-(4-morpholinyl)phenyl]-1-butanone, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone, methyl benzoylformate, benzoin dimethyl ether, diphenylacetophenone, α,α-dimethoxy-α-phenylacetophenone and 2,4-dihydroxybenzophenone.

[0045] In a specific embodiment provided by the present invention, the high hardness resin is EpoQuick from QMAXIS of the United States.

[0046] In another specific embodiment provided by the present invention, the high hardness resin is silicone resin Sanjin pigment SJ-60K.

[0047] According to the present invention, the content of the curing agent in the matte coating slurry is preferably 0 to 50 parts by weight, more preferably 0 to 45 parts by weight; when the high hardness resin in the matte coating slurry is a medium to low temperature curing epoxy resin, the content of the curing agent is not 0.

[0048] According to the present invention, the curing agent is any curing agent known to those skilled in the art without any particular limitation. In the present invention, it is preferably one or more of dicyandiamide curing agents, polyamide curing agents, tertiary amine curing agents, fatty amine curing agents, acid anhydride curing agents and imidazole curing agents; the dicyandiamide curing agent is preferably dicyandiamide; the polyamide curing agent is preferably aliphatic polyamide, aromatic polyamide and urea-formaldehyde polyamide; the tertiary amine curing agent is preferably one or more of imidazole, 1,2-dimethylimidazole, N-acylimidazole, pyridine, 4-dimethylaminopyridine and tetramethylethylenediamine ; The fatty amine curing agent is preferably one or more of diethylenetriamine, triethylenetetramine, ethylenediamine and hexamethylenediamine; the acid anhydride curing agent is preferably one or more of tetrahydrophthalic anhydride, hexahydrophthalic anhydride and methylhexahydrophthalic anhydride; the imidazole curing agent is preferably one or more of 2-methylimidazole (2MZ), 2-ethylimidazole (2-EI), 2-ethyl-4-methylimidazole (2E4MZ), 2-undecylimidazole (C11Z), 2-heptadecylimidazole (C17Z), 2-phenylimidazole (2PZ) and 1-benzyl-2-methylimidazole (1B2MZ).

[0049] According to the present invention, the content of the nanoparticles in the matte coating slurry is preferably 0.5-6 parts by weight, more preferably 0.5-5 parts by weight, further preferably 0.5-3 parts by weight, further preferably 0.5-2 parts by weight, and most preferably 0.8-1 part by weight.

[0050] According to the present invention, the particle size of the nanoparticles is preferably 3 to 200 nm; optionally, the particle size of the nanoparticles is 3 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm or a range between any two of the above values.

[0051] According to the present invention, the nanoparticles are nano heterogeneous structures; the nano heterogeneous structures are preferably complete or incomplete core-shell structures; the core of the nanoparticles is preferably mesoporous silica, and the shell is a black material; or, the core of the nanoparticles is a black material, and the shell is mesoporous silica; the present invention has no special restrictions on the shape of the core, which can be spherical, flower-shaped, flaky, rod-shaped, or linear, and at least one dimension is less than 100nm; the shell thickness of the core-shell structure is preferably 1-50nm, more preferably 1-40nm, more preferably 1-30nm, and most preferably 1-20nm; the black material is preferably one or more of carbon black, black quantum dots, ferroferric oxide, cobalt tetroxide, dopamine, graphene and carbon nanotubes.

[0052] In a specific embodiment provided by the present invention, the core of the nanoparticle is a black material and the shell is mesoporous silica. In this case, the nanoparticle is prepared according to the following steps: step 1) providing an alkaline aqueous solution containing a black material; step 2) dropping a silicate solution into the alkaline aqueous solution containing the black material for reaction to obtain nanoparticles; the mass concentration of the black material in the alkaline aqueous solution containing the black material in step 1) is preferably 0.1% to 1%, more preferably 0.1% to 0.5%, and more preferably 0.2% to 0.3%; the alkaline aqueous solution containing the black material in step S1) contains an alkaline substance; the alkaline substance is an alkaline substance well known to those skilled in the art, and there is no special limitation. In the present invention, it is preferably an alkali metal hydroxide. More preferably, it is sodium hydroxide; the concentration of the alkaline substance in the alkaline aqueous solution containing the black material is preferably 0.001-0.01 mol / L, more preferably 0.002-0.006 mol / L, and more preferably 0.004 mol / L; the solvent of the silicate solution is preferably alcohol, more preferably methanol; the volume ratio of the silicate to the solvent in the silicate solution is preferably 1:3-5, more preferably 1:3.5-1:4.5, and more preferably 1:4; the silicate can be a silicate well known to those skilled in the art, without any special restrictions, and is preferably tetraethyl silicate in the present invention; the reaction in the step 2) is preferably carried out at room temperature; in the present invention, nanoparticles of different particle sizes can be obtained by controlling the amount of the black material and the silicate solution.

[0053] In another specific embodiment provided by the present invention, the core of the nanoparticle is mesoporous silica and the shell is a black material. In this case, the nanoparticle is prepared according to the following steps: dispersing the mesoporous silica in an alcohol aqueous solution, then adding a surfactant and a carbon source for coating, and then calcining in a protective atmosphere to obtain nanoparticles; the alcohol aqueous solution is preferably an ethanol aqueous solution; the volume ratio of alcohol to water in the alcohol aqueous solution is preferably 1: (1-3), more preferably 1: (1.5-2.5), and more preferably 1: 2; the ratio of the mesoporous silica to the alcohol aqueous solution is preferably 1 mg: (5-10) mL, more preferably 1 mg: (6-8) mL, and more preferably 1 mg: (7 ~8)mL, most preferably 1mg:7.5mL; the dispersion method is preferably ultrasonic dispersion; the mass ratio of the mesoporous silica to the surfactant is preferably (10-50):1, more preferably (10-40):1, more preferably (15-35):1, more preferably (20-30):1, and most preferably 25:1; the surfactant can be a surfactant well known to those skilled in the art, without any special restrictions, and is preferably hexadecyltrimethylammonium bromide in the present invention; the carbon source can be a carbon source well known to those skilled in the art, without any special restrictions, and is preferably dopamine or resorcinol and formaldehyde in the present invention; the ratio of resorcinol to formaldehyde is preferably The coating is preferably carried out under alkaline conditions; the pH value of the alkaline conditions is preferably 7.5-9, more preferably 7.5-8.5; in the present invention, the alkaline conditions are preferably provided by ammonia water; the volume ratio of ammonia water to alcohol aqueous solution is preferably 1: (600-650), more preferably 1: (620-630), and more preferably 1: 625; the concentration of ammonia water is preferably 12-14 mol / L, more preferably 13-13.5 mol / L, and more preferably 14-15.5 mol / L. Preferably it is 13.38 mol / L; the coating is preferably carried out at 30°C to 40°C, more preferably at 35°C; the coating time is preferably 1 to 6 hours, more preferably 2 to 5 hours, and more preferably 3 to 4 hours; the protective atmosphere can be any protective atmosphere well known to those skilled in the art, without any special restrictions, and is preferably nitrogen in the present invention; the calcination temperature is preferably 800°C to 1000°C, more preferably 850°C to 950°C, and more preferably 900°C; the calcination time is preferably 0.5 to 2 hours, more preferably 1 to 2 hours; in the present invention, nanoparticles of different particle sizes can be obtained by adjusting the ratio of mesoporous silica to carbon source and the coating time.

[0054] According to the present invention, the surface of the nanoparticles is provided with a modification group or a modification layer; the modification group is preferably one or more of amino, epoxy, vinyl and thiol; the modification layer is preferably one or more of polyethyleneimine, polyvinyl alcohol, polyethylene glycol and paraffin. The dispersibility and stability of the nanoparticles in the matte coating slurry can be enhanced by providing the modification group or the modification layer.

[0055] In a specific embodiment provided by the present invention, a paraffin modification layer is provided on the surface of the nanoparticles; the preparation method thereof is specifically carried out according to the following steps: step 1) mixing the nanoparticles, paraffin and an emulsifier in an organic solvent to obtain a mixed solution A; step 2) adding the mixed solution A dropwise into deionized water under stirring to obtain an emulsion; step 3) continuously introducing silicon dioxide into the emulsion to obtain nanoparticles provided with a paraffin modification layer; the mass ratio of the nanoparticles to the paraffin is preferably 1:1-10, more preferably 1:3-8, more preferably 1:4-6, and most preferably 1:5; the mass ratio of the nanoparticles to the emulsifier is preferably 1:1-10, more preferably 1:4-8, and more preferably 1:6; the emulsifier can be an emulsifier well known to those skilled in the art, and there is no special limitation. The present invention The organic solvent is preferably an alkyl sulfate, more preferably sodium dodecyl sulfate (SDS); the organic solvent is any organic solvent known to those skilled in the art without any particular limitation, and in the present invention, N,N-dimethylcyclohexylamine is preferred; the ratio of the nanoparticles to the organic solvent is preferably 1 g: (100-300) mL, more preferably 1 g: (150-250) mL, and more preferably 1 g: 200 mL; the stirring speed in the step 2) is preferably 500-1000 pm, more preferably 600-1000 pm, more preferably 700-900 pm, and most preferably 800 pm; the flow rate of the carbon dioxide is preferably 50-100 mL / min, more preferably 60-100 mL / min, more preferably 70-90 mL / min, and most preferably 80 mL / min.

[0056] In another specific embodiment provided by the present invention, the surface of the nanoparticles is provided with a polymer modification layer, and the preparation method thereof is specifically carried out according to the following steps: after the nanoparticles are activated by a silane coupling agent, they are reacted with a polymer terminated with an active group to obtain nanoparticles provided with a polymer modification layer; the mass ratio of the nanoparticles to the silane coupling agent is preferably (1-10):1, more preferably (2-8):1, and more preferably (2-5):1; the silane coupling agent can be a silane coupling agent well known to those skilled in the art, and there is no special limitation. In the present invention, the silane coupling agent KH570 is preferably used; the ratio of the nanoparticles to the polymer terminated with an active group is preferably (1-10):1, more preferably (2-8):1, and more preferably (2-5):1. The mass ratio is preferably (1-10):3, more preferably (3-9):3, and more preferably (5-8):3; the polymer terminated with active groups is preferably a polymer terminated with epoxy groups; in the embodiment provided by the present invention, the polymer terminated with epoxy groups is preferably PEG terminated with epoxy groups, specifically taking Wengjiang reagent PA37695 as an example for explanation; the temperature for reacting with the polymer terminated with active groups is preferably 60°C-100°C, more preferably 70°C-90°C, and more preferably 80°C; the reaction time with the polymer terminated with active groups is preferably 1-10h, more preferably 3-8h, more preferably 4-6h, and most preferably 5h.

[0057] According to the present invention, since the nanoparticles include mesoporous silica having an anti-reflection function, the overall visible light reflectivity of the matte coating formed by the matte coating slurry is preferably less than 2%.

[0058] According to the present invention, the content of the hyperdispersant in the matte coating slurry is preferably 1 to 20 parts by weight, more preferably 5 to 20 parts by weight, and even more preferably 10 to 15 parts by weight.

[0059] According to the present invention, the hyperdispersant can be any hyperdispersant known to those skilled in the art without any particular limitation. In the present invention, it is preferably one or more of active derivatives based on a polyester main chain structure, polyurethane dispersants, copolymers of grafted polyacrylates and polyether dispersants, and more preferably one or more of EFKA-5010, EFKA-4050, EFKA-4060 of Efka, CH-6, CH-7, CH-8 of Shanghai Sanzheng, BYK-2000 of BYK, BASF PX4310, Sichuan Ona F431, Flowlen-33, 34 produced by KYOEISHA, and Tego-650, 651 of Degussa.

[0060] According to the present invention, the content of the dilution solvent in the matte coating slurry is preferably 5 to 15 parts by weight, more preferably 8 to 12 parts by weight, and even more preferably 10 parts by weight.

[0061] According to the present invention, the dilution solvent is any dilution solvent well known to those skilled in the art without any particular limitation. In the present invention, it is preferably one or more of toluene, xylene, n-hexane, ethyl acetate, ethanol, acetone, methyl ethyl ketone, cyclohexanone, methyl isobutyl ketone, ethylene glycol, chloroform, isopropanol, n-butanol, styrene, dibutyl phthalate, dioctyl phthalate, phenyl glycidyl ether, allyl glycidyl ether, p-cresol glycidyl ether, glycidyl methacrylate, ethylene glycol bisglycidyl ether, styrene oxide and alicyclic epoxy.

[0062] The present invention also provides a method for preparing the above-mentioned matte coating slurry, comprising the following steps: mixing 50 to 100 parts by weight of a high-hardness resin, 0 to 60 parts by weight of a curing agent, 0.1 to 8 parts by weight of nanoparticles, 0.1 to 20 parts by weight of a hyperdispersant and 5 to 20 parts by weight of a diluent to obtain a matte coating slurry.

[0063] The present invention has no special restrictions on the sources of all raw materials, and any raw materials available on the market can be used; the types and amounts of the high-hardness resin, curing agent, nanoparticles, hyperdispersant and diluent are the same as those described above and will not be repeated here.

[0064] According to the present invention, the mixing method is a method well known to those skilled in the art, and there is no particular limitation. In the present invention, high-speed dispersion is preferred; the mixing speed is preferably 1000-5000 rpm, more preferably 2000-4000 rpm, and more preferably 3000 rpm; the mixing time is preferably 10-60 min, more preferably 20-40 min, and more preferably 30 min.

[0065] The matte coating slurry provided by the present invention is a phase separation system. During the curing process of the coating material, the nanoparticles are neatly distributed on the surface of the coating material, thereby avoiding the ink color difference caused by the inconsistent spraying thickness of the coating material. Moreover, the nanoparticles cleverly combine the mesoporous silica with light diffusion and anti-reflection effects and the black nanoparticles with ink color improvement function at the nanoscale, so that a single nanoparticle integrates multiple functions such as light diffusion, anti-reflection, and blackness improvement, and further enables a single matte coating to have the effects of functional coatings such as anti-glare coating, anti-reflection coating, and black bottom filling coating at the same time, which not only effectively simplifies the production process, improves the product yield, but also greatly reduces the production cost; in addition, the nanoparticles only need a small amount of addition to play a corresponding ink color regulation effect, and the hardness and wear resistance of the coating material are guaranteed to the maximum extent; finally, the nanoparticles can provide an uneven microstructure for the matte coating to play an anti-glare effect, and at the same time, due to its nano-level particle size, it can effectively reduce the particle sedimentation caused by gravity, effectively improve the stability of the multifunctional matte coating slurry, and in addition, its nano size can also greatly improve the surface touch of the coating material.

[0066] The present invention also provides a matte coating formed by the above-mentioned matte coating slurry.

[0067] The matte coating slurry provided by the present invention is a phase separation system. During the curing process of the coating material, the nanoparticles are neatly arranged on the surface of the coating to form a microstructure layer, which can achieve an anti-glare effect through light diffusion.

[0068] According to the present invention, the thickness of the matte coating is preferably 3 to 30 microns, more preferably 5 to 30 microns, further preferably 10 to 30 microns, further preferably 10 to 20 microns, further preferably 10 to 15 microns, and most preferably 10 to 11 microns.

[0069] According to the present invention, the visible light reflectance of the matte coating is preferably less than 2%.

[0070] According to the present invention, the hardness of the matte coating can preferably reach 4H or above; the wear resistance of the matte coating can meet the requirements of more than 150 times of steel wool friction.

[0071] The present invention also provides an LED display module, comprising a substrate, a plurality of LED light-emitting chips arranged on the substrate, a transparent packaging layer arranged between and on the upper surface of the plurality of LED light-emitting chips, a black light-transmitting adhesive film layer arranged on the transparent packaging layer, and a matte coating layer arranged on the black light-transmitting adhesive film layer; the matte coating layer is formed by the above-mentioned matte coating slurry.

[0072] See also Figure 1 , Figure 1This is a schematic diagram of the cross-sectional structure of the LED display module provided by the present invention, wherein 100 is a substrate, 200 is an LED light-emitting chip, 300 is a transparent encapsulation layer, 400 is a black light-transmitting film layer, and 500 is a matte coating.

[0073] According to the present invention, the substrate can be any substrate well known to those skilled in the art without any special limitation. In the present invention, a PCB substrate is preferred.

[0074] According to the present invention, a plurality of LED light-emitting chips are arranged on the substrate; the distance between the plurality of LED light-emitting chips is preferably 0.2 to 2 mm, more preferably 0.5 to 1.5 mm, and even more preferably 0.9 to 1 mm.

[0075] According to the present invention, a transparent encapsulation layer is provided between the plurality of LED light-emitting chips and on their upper surfaces; the transparent encapsulation layer can be a transparent encapsulation layer well known to those skilled in the art, and there is no special limitation. In the present invention, it preferably includes one or more of epoxy resin, acrylic resin, silicone and polyurethane; in the embodiment provided by the present invention, transparent modified epoxy resin is specifically used. Take an example to illustrate; the thickness of the transparent encapsulation layer on the upper surface of the LED light-emitting chip is preferably 0.1-1 mm, more preferably 0.3-0.8 mm, more preferably 0.4-0.6 mm, and most preferably 0.5 mm.

[0076] According to the present invention, a black light-transmitting adhesive film layer is arranged on the transparent encapsulation layer; the thickness of the black light-transmitting adhesive film layer is preferably 10-200 μm, more preferably 30-100 μm, more preferably 50-100 μm, and most preferably 75 μm. The black light-transmitting adhesive film layer preferably includes one or more of polyimide (PI), polycarbonate (PC), polyethylene terephthalate (PET) and triacetyl cellulose (TAC); the black light-transmitting adhesive film layer can be a double-sided adhesive film or a matte adhesive film, and there is no special restriction; the visible light transmittance of the black light-transmitting adhesive film layer is preferably greater than 30%, more preferably 35%-85%, more preferably 35%-70%, more preferably 35%-60%, and most preferably 50%; in the embodiments provided by the present invention, the black PET film of Pingyu New Materials is specifically taken as an example for explanation.

[0077] According to the present invention, a matte coating is provided on the black light-transmitting adhesive film layer; the matte coating is formed by the above-mentioned matte coating slurry; the thickness of the matte coating is preferably 3 to 30 microns, more preferably 5 to 30 microns, further preferably 10 to 30 microns, and most preferably 10 to 20 microns.

[0078] According to the present invention, the overall visible light transmittance of the LED display module is preferably greater than 30%, more preferably 35% to 85%, more preferably 35% to 70%, more preferably 35% to 60%, more preferably 40% to 60%, more preferably 45% to 55%, and most preferably 47% to 50%.

[0079] The present invention also provides a method for preparing the above-mentioned LED display module, comprising the following steps: S1) fixing a plurality of LED light-emitting chips on a substrate, and then performing integrated packaging to form a transparent packaging layer; S2) laminating a black light-transmitting adhesive film layer on the transparent packaging layer; S3) performing surface plasma treatment on the substrate laminating the black light-transmitting adhesive film layer, and then applying a matte coating slurry, and after curing, obtaining an LED display module.

[0080] According to the present invention, in the step S1), the LED light-emitting chip is fixed by a die bonding wire process.

[0081] According to the present invention, the integrated package preferably uses a dam + molding process; the integrated package is preferably first cured at a high temperature and then cured at room temperature; the high temperature is preferably 100°C to 150°C, more preferably 110°C to 140°C, and more preferably 120°C to 130°C; the curing time at the high temperature is preferably 1 to 10 minutes, more preferably 3 to 6 minutes, and more preferably 5 minutes; the curing time at room temperature is preferably 8 to 20 hours, more preferably 10 to 15 hours, and more preferably 12 hours.

[0082] According to the present invention, the power of the surface plasma treatment is preferably 100-300 W, more preferably 150-250 W, and more preferably 200 W; the time of the surface plasma treatment is preferably 10-30 s, more preferably 15-25 s, and more preferably 20 s.

[0083] According to the present invention, the method of applying the matte coating slurry in step S3) can be a method well known to those skilled in the art, and there is no special limitation. In the present invention, it can be spraying or roller coating; the number of times of coating can be one word or multiple times to achieve the desired thickness.

[0084] According to the present invention, the curing method in step S3) can be selected according to the type of high hardness resin in the matte coating slurry; in the present invention, it is preferred to perform heating curing and then room temperature curing; the temperature of the heating curing is preferably 100°C to 150°C, more preferably 100°C to 130°C, and more preferably 100°C to 120°C; the time of the heating curing is preferably 10 to 60 minutes, more preferably 20 to 40 minutes, more preferably 25 to 35 minutes, and most preferably 30 minutes; the time of the room temperature curing is preferably 20 to 60 hours, more preferably 40 to 50 hours, and more preferably 48 hours.

[0085] In a specific embodiment provided by the present invention, the LED display module is arranged according to Figure 2 The preparation was carried out according to the preparation process schematic diagram shown.

[0086] In the present invention, unless otherwise specified, parts are parts by weight.

[0087] In order to further illustrate the present invention, a matte coating slurry, a matte coating and an LED display module provided by the present invention are described in detail below in combination with embodiments.

[0088] The reagents used in the following examples are all commercially available.

[0089] Example 1

[0090] 1.1 Preparation of multifunctional nanoparticles

[0091] Sodium citrate was used as a surfactant and reduced by ethylene glycol at 200°C. That is, 0.2g of FeCl3·6H2O was dissolved in 40mL of ethylene glycol to prepare a uniform solution, 0.4g of sodium citrate was added under vigorous stirring, and then 2.4g of sodium acetate was added and stirred for 1h. After that, the mixed solution was transferred to a stainless steel autoclave and placed in a 200°C oven for reaction for 8h. The product was collected by magnetic separation and washed several times with ethanol and water. By controlling the concentration of the reactants and the reaction time, ferroferric oxide nanoparticles with a particle size of 15nm were prepared.

[0092] 0.1 g of the above-mentioned 15 nm ferroferric oxide nanoparticles was dispersed in 50 mL of deionized water, and after adding 2 mL of 0.1 M sodium hydroxide solution, 1.1 mL of tetraethyl silicate (TEOS) methanol solution (1 / 4, v / v) was added dropwise. The reaction was carried out at room temperature for 24 hours to prepare ferroferric oxide nanohybrid particles Fe3O4@SiO2 with a surface coated with mesoporous silica with a thickness of 10 nm.

[0093] 0.1 g of Fe3O4@SiO2, 0.5 g of paraffin (Sinopec, MVI500) and 0.6 g of emulsifier SDS were dispersed in 20 mL of N,N-dimethylcyclohexylamine and stirred until the emulsifier and paraffin were completely dissolved to prepare a mixed solution A; under stirring at 800 rpm, the mixed solution A was added dropwise into deionized water to prepare an O / W emulsion, and a carbon dioxide gas flow at a flow rate of 80 mL / min was continuously introduced into the emulsion to precipitate the paraffin, thereby preparing paraffin-coated multifunctional nanoparticles Fe3O4@SiO2@paraffin.

[0094] See also Figure 3 , Figure 3 Schematic diagram of the structure of paraffin-coated multifunctional nanoparticles Fe3O4@SiO2@paraffin.

[0095] The multifunctional nanoparticles SiO2@C-PEG modified by PEG were analyzed by scanning electron microscopy, and the scanning electron microscopy image was obtained as follows: Figure 4 shown.

[0096] 1.2 Preparation of multifunctional matte coating

[0097] Take 70 parts of high-hardness modified epoxy resin EpoQuick from QMAXIS, USA, 45 parts of methyl hexahydrophthalic anhydride, anhydride curing agent from Jinan Sunny Chemical, 1 part of multifunctional nanoparticles Fe3O4@SiO2@paraffin prepared in 1.1, 10 parts of BASF PX4310 superdispersant, and 10 parts of diluent acetone, use a high-speed dispersing machine to disperse at 3000rpm for 30 minutes to prepare a multifunctional matte coating slurry.

[0098] 1.3 Preparation of LED display screen with high ink color consistency

[0099] Fix several LED light-emitting chips on the LED driver board through the die bonding wire process, with a dot pitch of 0.9mm, and detect whether they pass the lighting test;

[0100] Using the dam + molding process, the transparent modified epoxy resin After centrifugal degassing, it is used to perform integrated packaging on the surface of the light-emitting chip. The packaging film thickness is 0.5 mm. After high-temperature curing at 120°C for 5 minutes, it is cured at room temperature for 12 hours.

[0101] Using a dicing machine to cut the process edge of the LED display unit to prepare an LED display module of standard size;

[0102] A vacuum laminating machine is used to laminate a black light-transmitting adhesive film layer onto the surface of the standard-sized LED display module prepared above. The black light-transmitting adhesive film layer used is a black PET film (Pingyu New Materials, 75 μm) with a visible light transmittance of 50%;

[0103] The LED display module with black PET film was subjected to surface plasma treatment at 200W for 20s.

[0104] Using an inkjet process, a layer of the multifunctional matte coating slurry prepared in 1.2 with a wet thickness of about 10 μm was sprayed on the surface of the PET film. After curing at 100°C for 30 minutes and then at room temperature for 48 hours, an LED display module with high ink color consistency was obtained.

[0105] Example 2

[0106] 2.1 Preparation of multifunctional nanoparticles

[0107] Isopropanol (6 mL), ethanol (50 mL) and water (10 mL) were prepared into a mixed solution and stirred thoroughly. TEOS solution (50 μL) was added under high-speed stirring and stirred thoroughly for 30 min. Ammonia solution (4.5 mL) was added dropwise and reacted at room temperature for 30 min to prepare mesoporous SiO2 nanoparticles with a particle size of 20 nm.

[0108] Mesoporous SiO2 (500 mg) nanoparticles were added to a mixture of anhydrous ethanol (125 mL) and deionized water (250 mL) under stirring, and ultrasonically dispersed for 3 min. 20 mg of hexadecyltrimethylammonium bromide, resorcinol (750 mg), and 0.6 mL of ammonia water (13.38 mol / L) were added, and stirring was continued for 30 min. 1 mL of formaldehyde was added, and the mixture was stirred and reacted at 35°C for 3 h. The product was washed several times with deionized water and ethanol, dried to constant weight at 60°C, and calcined at 900°C for 1 h under a nitrogen atmosphere to obtain multifunctional nanoparticles SiO2@C, in which the C shell thickness was 10 nm. After being activated with 200 mg of silane coupling agent KH570, it was reacted with 300 mg of epoxy-terminated PEG (Wengjiang reagent, PA37695) at 80°C for 5 h to prepare PEG-modified multifunctional nanoparticles SiO2@C-PEG.

[0109] See also Figure 5 , Figure 5 Schematic diagram of the structure of PEG-modified multifunctional nanoparticles SiO2@C-PEG.

[0110] The multifunctional nanoparticles SiO2@C-PEG modified by PEG were analyzed by scanning electron microscopy, and the scanning electron microscopy image was obtained as follows: Figure 6 shown.

[0111] 2.2 Preparation of multifunctional matte coating

[0112] Take 80 parts of high-hardness silicone resin (Sanjin Pigment SJ-60K), 0.8 parts of multifunctional nanoparticles SiO2@C-PEG prepared in 2.1, 15 parts of superdispersant (Sichuan Ona F431), and 10 parts of diluent acetone, and disperse them at 3000rpm for 30 minutes using a high-speed disperser to prepare a multifunctional matte coating slurry.

[0113] 2.3 Preparation of LED display screen with high ink color consistency

[0114] Same as Example 1.

[0115] Example 3

[0116] The particle size of the prepared mesoporous SiO2 nanoparticles is 200 nm, and the rest is the same as in Example 2.

[0117] Comparative Example 1

[0118] 1.1 Preparation of multifunctional matte coating

[0119] Take 70 parts of high-hardness modified epoxy resin EpoQuick, 45 parts of anhydride curing agent (Qingtian Chemical, methylhexahydrophthalic anhydride), 1 part of mesoporous SiO2 nanoparticles with a diameter of 20nm, 1 part of carbon black with a particle size of 20nm, 10 parts of hyperdispersant BASF PX4310, and 10 parts of diluent solvent acetone, and disperse them at 3000rpm in a high-speed disperser for 30 minutes to prepare a multifunctional matte coating slurry.

[0120] 1.2 Preparation of LED display screen with high ink color consistency

[0121] Same as Example 1.

[0122] Comparative Example 2

[0123] 2.1 Preparation of multifunctional matte coating

[0124] Take 80 parts of high-hardness silicone resin (Sanjin Pigment SJ-60K), 1 part of mesoporous SiO2 nanoparticles with a diameter of 200nm, 1 part of carbon black with a particle size of 95nm, 15 parts of super dispersant (Sichuan Ona F431), and 10 parts of diluent solvent acetone, and disperse them at 3000rpm in a high-speed disperser for 30 minutes to prepare a multifunctional matte coating slurry.

[0125] 2.2 Preparation of LED display screen with high ink color consistency

[0126] Same as Example 1.

[0127] Performance Testing

[0128] 1. Ink color consistency test

[0129] Three LED display screens prepared using the above-mentioned embodiment and comparative example process methods were tested for ink color consistency. A colorimeter was used to test the L value at nine different positions of the light board. The ink color consistency within the light board and between the light boards was compared. The results are shown in Table 1.

[0130] Table 1 Ink color consistency test results

[0131]

[0132]

[0133]

[0134] It can be seen from the data in Table 1 that, compared with Comparative Examples 1 and 2, the ink color consistency differences within the lamp boards and between the lamp boards of Examples 1 to 3 are smaller.

[0135] 2. Matt coating thickness, reflectivity, surface hardness, wear resistance and light transmittance test

[0136] Matt coating thickness test: The thickness of the matte coating was measured using a microscope, and the results are shown in Table 2.

[0137] Reflectivity test: Fix the light panels on the box and use a reflectivity meter to measure the reflectivity of each group of light panels at 550nm. The results are shown in Table 2.

[0138] Surface hardness test: Fix the light panels on the box and use a pencil hardness tester to measure the surface hardness of each group of light panels. The load weight is 500g. The test results are shown in Table 2.

[0139] Abrasion resistance test: Use a wool felt test head, apply a load of 1000g, and rub back and forth on the surface of each group of light panels 2000 times with a stroke of 40mm at a constant rate (40cycle / min). After the test, observe whether the surface is white or scratched. The results are shown in Table 2.

[0140] Transmittance test: The brightness of the comparative example and the example LED module after being encapsulated in the transparent encapsulation layer is between 1250-1300 cd / m 2 The light transmittance is calculated by the measured brightness after spraying the matte coating (B2) / brightness after encapsulation with the transparent encapsulation layer (B1)×100%. The results are shown in Table 2.

[0141] Table 2 Test results of reflectivity, surface hardness and wear resistance

[0142]

[0143]

[0144] It can be seen from Table 2 that the reflectivity of each group can be controlled within 2.5%, but the reflectivity difference between the lamp boards of Example 1, Example 2, and Example 3 is smaller; the surface hardness of the lamp boards of Example 1, Example 2, and Example 3 is significantly higher than that of Comparative Example 1 and Comparative Example 2. This is because the number of nanoparticles added in Comparative Example 1 and Comparative Example 2 is too high, which greatly reduces the hardness of the high-hardness resin; similarly, due to the excessive number of nanoparticles added, the wear resistance of Comparative Example 1 and Comparative Example 2 is significantly reduced.

[0145] In summary, the LED display module provided by the present invention has the following advantages:

[0146] 1) The ink color consistency of the module is mainly determined by the substrate color and the surface reflectivity. In the LED display module provided by the present invention, the black light-transmitting adhesive film layer can partially shield the ink color of the PCB substrate, and the multifunctional matte coating can not only play the role of a black coating, but also play the role of light diffusion and anti-reflection, which can effectively improve the ink color consistency of the display module.

[0147] 2) In the LED display module provided by the present invention, the multifunctional matte coating used is a phase separation system. During the curing process of the coating material, the multifunctional nanoparticles are neatly distributed on the surface of the coating material, avoiding the ink color difference caused by inconsistent spraying thickness of the coating material.

[0148] 3) The LED display module provided by the present invention has only a black light-transmitting adhesive film layer and a multifunctional matte coating on the transparent encapsulation layer, and the production process is simple and easy to rework, which greatly reduces the production cost of improving the consistency of the module appearance.

[0149] 4) The nanoparticles designed in the present invention cleverly combine mesoporous silica with light diffusion and anti-reflection effects and black nanoparticles with ink color improvement function at the nanoscale, so that a single nanoparticle integrates multiple functions such as light diffusion, anti-reflection, and blackness improvement. Further, a single multifunctional matte coating has the effects of functional coatings such as anti-glare coating, anti-reflection coating, and black underfill coating, which effectively simplifies the production process, improves product yield, and greatly reduces production costs.

[0150] 5) Since nanoparticles have multiple functions such as light diffusion, anti-reflection, and blackness enhancement, the multi-layer coating materials that originally needed to be covered during packaging are simplified and integrated into a single-layer coating material, avoiding the overlapping coating of multiple layers of adhesive films or resin materials and increasing the surface hardness of the coating material.

[0151] 6) An increase in the amount of nanoparticles added often results in a rapid decrease in mechanical properties such as hardness and wear resistance of the resin material. Due to the ingenious design of the multifunctional nanoparticles in the present invention, only a very small amount of addition is required to achieve the corresponding ink color regulation effect, thereby ensuring the hardness and wear resistance of the coating material to the maximum extent.

[0152] 7) The particle size of the multifunctional nanoparticles designed in the present invention is between 3-200 nanometers, which can provide an uneven microstructure for the multifunctional matte coating to achieve an anti-glare effect. At the same time, due to its nano-scale particle size, it can effectively reduce the particle sedimentation caused by gravity, effectively improving the stability of the multifunctional matte coating material. In addition, its nano-size can also greatly improve the surface touch of the coating material.

[0153] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A matte coating slurry, characterized in that: include: 50 to 100 parts by weight of high hardness resin; Curing agent 0-60 parts by weight; 0.1 to 8 parts by weight of nanoparticles; 0.1 to 20 parts by weight of hyperdispersant; 5 to 20 parts by weight of diluent; The nanoparticles are nano heterogeneous structures; The nanoparticles include mesoporous silica and a black material.

2. The matte coating slurry according to claim 1, characterized in that: The particle size of the nanoparticles is 3 to 200 nm.

3. The matte coating slurry according to claim 1, characterized in that: The black material is selected from one or more of carbon black, black quantum dots, ferroferric oxide, cobalt trioxide, dopamine, graphene and carbon nanotubes.

4. The matte coating slurry according to claim 1, characterized in that: The nanoparticles are of core-shell structure; The core of the nanoparticle is mesoporous silica, and the shell is a black material; Alternatively, the core of the nanoparticle is a black material and the shell is mesoporous silica; The shell thickness of the nanoparticles is 1 to 50 nm.

5. The matte coating slurry according to any one of claims 1 to 4, characterized in that: The surface of the nanoparticle is provided with a modification group or a modification layer; the modification group is selected from one or more of an amino group, an epoxy group, a vinyl group and a thiol group; The modified layer is selected from one or more of polyethyleneimine, polyvinyl alcohol, polyethylene glycol and paraffin.

6. The matte coating slurry according to claim 1, characterized in that: The high hardness resin is selected from one or more of medium and low temperature curing epoxy resin, moisture curing resin, UV curing resin and acrylic resin; The medium and low temperature curing epoxy resin is selected from one or more epoxy resins with one or more of dicyandiamide curing agents, polyamide curing agents, tertiary amine curing agents, fatty amine curing agents, acid anhydride curing agents and imidazole curing agents as curing agents; The moisture-curable resin is selected from one or more of epoxy resin, silicone resin and polyurethane resin; The UV curable resin is selected from acrylate resin; The curing agent is selected from one or more of dicyandiamide curing agents, polyamide curing agents, tertiary amine curing agents, fatty amine curing agents, acid anhydride curing agents and imidazole curing agents; The super dispersant is selected from one or more of active derivatives based on a polyester main chain structure, polyurethane dispersants, grafted polyacrylate copolymers and polyether dispersants; The diluting solvent is selected from one or more of toluene, xylene, n-hexane, ethyl acetate, ethanol, acetone, methyl ethyl ketone, cyclohexanone, methyl isobutyl ketone, ethylene glycol, chloroform, isopropanol, n-butanol, styrene, dibutyl phthalate, dioctyl phthalate, phenyl glycidyl ether, allyl glycidyl ether, p-cresol glycidyl ether, glycidyl methacrylate, ethylene glycol bisglycidyl ether, styrene oxide and alicyclic epoxy.

7. A matte coating, characterized in that: The matte coating slurry is formed from the matte coating slurry according to any one of claims 1 to 6.

8. The matte coating according to claim 7, characterized in that: The thickness of the matte coating is 3 to 30 microns; The visible light reflectivity of the matte coating is less than 2%.

9. An LED display module, characterized in that: It comprises a substrate, a plurality of LED light-emitting chips arranged on the substrate, a transparent packaging layer arranged between and on the upper surface of the plurality of LED light-emitting chips, a black light-transmitting adhesive film layer arranged on the transparent packaging layer, and a matte coating layer arranged on the black light-transmitting adhesive film layer; the matte coating layer is formed by the matte coating slurry described in any one of claims 1 to 6.

10. The LED display module according to claim 9, characterized in that: The overall visible light transmittance of the LED display module is greater than 30%; The visible light transmittance of the black light-transmitting adhesive film layer is greater than 30%.